2016
DOI: 10.1016/j.jmr.2016.01.015
|View full text |Cite
|
Sign up to set email alerts
|

On the present and future of dissolution-DNP

Abstract: Dissolution-DNP is a method to create solutions of molecules with nuclear spin polarization close to unity. The many orders of magnitude signal enhancement have enabled many new applications, in particular in vivo MR metabolic imaging. The method relies on solid state dynamic nuclear polarization at low temperature followed by a dissolution to produce the room temperature solution of highly polarized spins. This work describes the present and future of dissolution-DNP in the mind of the author. The article des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
337
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(347 citation statements)
references
References 47 publications
7
337
1
2
Order By: Relevance
“…9 In dissolution DNP, nuclear spins are polarized in the solid state and subsequently dissolved rapidly, resulting in a "hyperpolarized" room-temperature liquid yielding liquid-state signal enhancements of typically more than 10 000-fold. 9,10 Using this technology, samples containing low-γ nuclei such as 13 C may be both highly polarized and physiologically compatible, allowing for biomedical applications such as 13 C metabolic imaging in real-time. [11][12][13][14][15] The efficiency of DNP is highly dependent on the sample composition and physical conditions under which it takes place.…”
Section: Introductionmentioning
confidence: 99%
“…9 In dissolution DNP, nuclear spins are polarized in the solid state and subsequently dissolved rapidly, resulting in a "hyperpolarized" room-temperature liquid yielding liquid-state signal enhancements of typically more than 10 000-fold. 9,10 Using this technology, samples containing low-γ nuclei such as 13 C may be both highly polarized and physiologically compatible, allowing for biomedical applications such as 13 C metabolic imaging in real-time. [11][12][13][14][15] The efficiency of DNP is highly dependent on the sample composition and physical conditions under which it takes place.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] Many DNP optimization studies reported previously were performed at magnetic elds of 3.35 T, mainly due to the availability of commercial hyperpolarizer operating at 3.35 T (Hypersense, Oxford Instruments, UK) and W-band microwave source. Recent work has shown greater DNP-enhanced polarization levels can be gained at elds of 5-7 T 22-25 and a recent DNP hyperpolarizer for clinical purposes (SPINlab™, GE Healthcare, WI) has an operating eld of 5 T. 26 Therefore, greater exploration of suitable sample conditions for optimal polarization properties at these elds are needed, especially as the electronic properties of free radicals change with eld. 27 In this article, we have investigated the inuence of glassing solvent deuteration and the inclusion of Gd 3+ on 13 C DNP at a eld of 5 T. Free radicals 4-oxo-TEMPO and trityl OX063 ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Tangible progress has been made towards the goals of developing affordable HP MRI biomedical applications and robust use of this technology in human studies [275,276]. …”
Section: Resultsmentioning
confidence: 99%